2024
DOI: 10.3389/fimmu.2024.1328820
|View full text |Cite
|
Sign up to set email alerts
|

Specific T-cell subsets have a role in anti-viral immunity and pathogenesis but not viral dynamics or onwards vector transmission of an important livestock arbovirus

Kerry Newbrook,
Nakibul Khan,
Aimee Fisher
et al.

Abstract: IntroductionBluetongue virus (BTV) is an arthropod-borne Orbivirus that is almost solely transmitted by Culicoides biting midges and causes a globally important haemorrhagic disease, bluetongue (BT), in susceptible ruminants. Infection with BTV is characterised by immunosuppression and substantial lymphopenia at peak viraemia in the host.MethodsIn this study, the role of cell-mediated immunity and specific T-cell subsets in BTV pathogenesis, clinical outcome, viral dynamics, immune protection, and onwards tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…( 25 27 ) suggest that epitopes from NS1, VP2 and VP7 proteins of BTV can induce cross-reactive CD4+ and CD8+ T cell responses against multiple BTV serotypes. Similarly, many other studies have demonstrated the importance of CD4+ and CD8+ T cells that recognize epitopes on structural (VP2 and VP7) and non-structural (NS1) BTV proteins in conferring protection against BT ( 23 , 24 , 28 30 ). In light of these findings, vaccination designed to elicit cross-reactive T cell responses holds the potential to protect animals against several BTV serotypes.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…( 25 27 ) suggest that epitopes from NS1, VP2 and VP7 proteins of BTV can induce cross-reactive CD4+ and CD8+ T cell responses against multiple BTV serotypes. Similarly, many other studies have demonstrated the importance of CD4+ and CD8+ T cells that recognize epitopes on structural (VP2 and VP7) and non-structural (NS1) BTV proteins in conferring protection against BT ( 23 , 24 , 28 30 ). In light of these findings, vaccination designed to elicit cross-reactive T cell responses holds the potential to protect animals against several BTV serotypes.…”
Section: Introductionmentioning
confidence: 70%
“…Notably, BTV infections elicit serotype-specific neutralizing antibodies primarily against the outer capsid, which exhibits significant variability across serotypes ( 29 , 39 ), prompting the exclusion of B cell epitopes in our broad-spectrum vaccine design. Furthermore, we selected the non-structural proteins of BTV as promising vaccine targets because they are highly conserved and are also the dominant source for T cell epitopes, particularly NS1 protein ( 1 – 3 , 8 , 10 , 11 , 13 , 15 19 , 21 , 22 , 24 , 27 , 30 , 33 36 , 38 87 ) ( 22 , 29 ). Additionally, we performed protein-protein docking and molecular dynamics simulations (MDS) to study the molecular interaction patterns and investigate the vaccine’s capacity to trigger an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The most-utilized CoPs are neutralizing antibody (Nab) titers, with higher antibody titers commonly linked to increased protection ( Figures 1E, F ). Reduced viral loads and the absence of clinical disease have consistently been associated with higher Nab titers following passive immunization or vaccination against FMDV (sheep, cattle, and pigs) ( 62 64 , 81 ), PRRSV ( 15 , 32 , 51 , 54 , 55 ), BTV ( 15 , 26 , 27 , 31 ), and CSFV ( 107 , 110 , 111 , 117 , 120 ) ( Table 1 ). Sterilizing immunity is associated with high Nab titers for PRRSV ( 54 , 186 ), CSFV ( 187 ), and BTV ( 188 , 189 ).…”
Section: Humoral Immune Features As Correlates Of Protectionmentioning
confidence: 99%
“…CD4+ T cells have a key role in generating strong protective humoral immunity through the development of T cell-dependent antibody responses against BTV ( 211 ), ASFV ( 212 ), and FMDV ( 213 ) and should be investigated for CSFV, PRRSV, and LSDV ( Table 1 ). Notably, the depletion of CD4+ helper T cells in sheep enhanced clinical signs of BTV primary infection and impaired the development of Nabs, thus highlighting the importance of these cells in the development of protective antibody-mediated immunity ( 31 ). The level of T-cell dependency for generating an antibody response is likely antigen dependent ( 31 ).…”
Section: Cellular Immune Features As Correlates Of Protectionmentioning
confidence: 99%
See 1 more Smart Citation